Current Federal Reserve policy under the lens of economic history : essays to commemorate the Federal Reserve System's centennial - Humpage, Owen F. (Cambridge : Cambridge University Press, 2015)
In December 2012, as a kick-off to the Federal Reserve System's centennial, the Federal Reserve Bank of Cleveland asked leading monetary historians and macroeconomic economists to address current and recurring economic concerns that confront central banks from a historical perspective. The resulting papers, published in this volume, cover a wide range of issues, including the meaning of central-bank independence, the role of communications and rules in fostering credibility, the evolution of the lender-of-last-resort function, the mechanism through which banks transmit economic shocks, and prospects for a European monetary union. A retrospective on the Federal Reserve, this book contains essays by some of the world's most prominent financial historians and provides a thorough overview of the evolution of the monetary standard over the past two centuries. Offering historical context as a complement to economic theory and empiricism, these papers investigate how financial infrastructure shapes economic outcomes through comparisons of Canada and the United States.
Introduction : Context and content / Owen F. Humpage -- The uses and misuses of economic history / Barry Eichengreen -- Federal reserve policy today in historical perspective / Marvin Goodfriend -- How and why the Fed must change in its second century / Allan H. Meltzer -- The lender of last resort : lessons from the Fed's first 100 years / Mark A. Carlson and David C. Wheelock -- Close but not a central bank : the New York clearing house and issues of clearing house loan certificates / Jon Moen and Ellis Tallman -- Central Bank independence : can it survive a crisis? / Forrest Capie and Geoffrey Wood -- Politics on the road to the U.S. monetary union / Peter L. Rousseau -- U.S. precedents for Europe / Harold James -- The limits of bimetallism / Christopher M. Meissner -- The reserve pyramid and interbank contagion during the Great Depression / Kris James Mitchener and Gary Richardson -- Would large-scale asset purchases have helped in the 1930s? An investigation of the responsiveness of bond yields from the 1930s to changes in debt levels / John Landon-Lane -- A tale of two countries and two booms, Canada and the United States in the 1920s and 2000s : the roles of monetary and financial stability policies / Ehsan U. Choudhri and Lawrence L. Schembri -- It is history but it's no accident : differences in residential mortgage markets in Canada and the United States / Angela Redish -- Monetary regimes and policy on a global scale : the oeuvre of Michael D. Bordo / Hugh Rockoff and Eugene N. White -- Reflections on the history and future of central banking / Michael D. Bordo.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: United States. -- Federal Reserve Board; Federal Reserve banks; Monetary policy -- United States; United States -- Economic policy